Debate: What Would be the Best Way to Use 10 Million Dollars in the Counter-Trafficking Sector? - Friedman, Matt (Anti-Trafficking Review, 2014)
For me, it is essential that the first question related to this query be: ‘What are we really hoping to achieve with our available resources?’ In the past, this question would have been answered in terms of the deployment of the traditional ‘3 Ps’: prevention interventions, prosecution efforts and protection initiatives. Programme efforts under these headings are often designed to prevent people from being trafficked, put criminals in jail and help victims after they leave the exploitative environment. But few interventions explicitly state ‘the goal is to reduce the number of people in human trafficking/slavery-like conditions’. The goal must be the reduction of overall victims. The second question I would ask: ‘What can be done to achieve the most impact in reducing the number of trafficked persons, with the least amount of resources?’ In other words, I would seek to put in place a programme that is both cost effective and impactful. With limited funding available globally, every dollar must count.